Analysis for military decisions - Quade, E.S (MORS heritage series, 2000)
Presentation of the lectures prepared for the RAND course "An appreciation of analysis for military decisions." The lectures are designed primarily for decisionmakers and not for analysts; they are not intended to teach systems analysis, but to point out the weaknesses and possible abuses, as well the effectiveness, of an analytic approach to long-range military planning.